(3eHGQb GdCRgGQ aj TQM eTGQb GdCfhGQs - (3YHO GddWja Hf YHO GdYRjR Hf Cejf GdOjf Hf aQTJG GdcQeGfj, GdeYQha HGHf edc , (B801 (3g`s ((3bSWfWjfjIs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg Ydi gOjI GdgOGjI hGdESdGe heeG Ufa ajg ef GdcJH GdaGNQI cJGH eTGQb GdCfhGQ aj UMGM GdCNHGQ hcGfJ dg TQhM aUQJ COjQ aj faSj hCSJNjQ Gddg aj jhej hCeSj Cf CTQMg TQMG jNHQ Yf NHGjG YHGQGJg s
(3BNQgG (B:s
(3cGf jdHj HgPg GdJdHjI aj MLg hYeQJg (B((3e (B) (3CfS Qhi eSde Yfg (B: (3dHjc YeQI hMLG efUhH HebOQ Cj eQjOG YeQI Ch HfRY GdNGaV Cj HYeQI gPG jOd Ydi Cfg cGf bGQfGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 59s
(3eYLe GdeDdajf (B2 / 215s
(3cTa GdXfhf (B2 / 1689s
(3TPQGJ GdPgH (B7 / 342s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs